The immune system contributes to the effectiveness of vaccine therapy in patients with metastatic melanoma - I. N. Mikhaylova; M. N. Stakheyeva; I. Zh. Shubina; G. Z. Chkadua; A. A. Borunova; R. A. Zukov; I. V. Bogdashin; E. L. Choynzonov; N. V. Cherdyntseva (Сибирский онкологический журнал)
The aim of the study was to identify differences in the immune system parameters between metastatic melanoma patients who responded and did not respond to dendritic cell vaccination.Material and Methods. The study group included 20 patients with stage III–IV metastatic melanoma, who received vaccine therapy with dendritic cells (DC) in a prophylactic mode. The control groups included 13 patients who had symptoms of disease progression at the time of starting vaccine therapy, and 5 healthy donors. The DC-vaccine was prepared in the form of a suspension of the patient’s autologous dendritic cells loaded with tumor antigens in vitro. A single dose had 2 million dendritic cells in 1 ml of phosphate buffer solution, which was administered intradermally in the nearest site to the regional lymphatic collectors. The immune system status was assessed before starting vaccination. The immune system status was evaluated according to the indices of 25 peripheral blood cell populations using multicolor flow cytometry and integral characteristic in the form of the visual image generated by the visualization method of multidimensional data (NovoSpark, Canada).Results. The immune status in patients with metastatic melanoma at the start of DC-vaccination differed and was associated with the effectiveness of subsequent vaccine therapy. The response to vaccination was observed in patients whose immune system status was similar to that of healthy individuals. Low efficacy of DC-vaccine therapy was shown in patients whose immune system status corresponded to that of patients with disease progression. Alterations of the immune system in patients with metastatic melanoma were registered both at the level of individual immunological parameters and at the level of visualized integral characteristics. The integral characteristics of the immune system associated with the patient’s immunocompromised status can be considered as a criterion for stratification of patients with metastatic melanoma for the effective DC-vaccine therapy.Conclusion. The effectiveness of vaccine therapy with dendritic cells in patients with metastatic melanoma is associated with the immune system state before starting this therapy.